2001
DOI: 10.1074/jbc.m009596200
|View full text |Cite
|
Sign up to set email alerts
|

Thioflavin T Is a Fluorescent Probe of the Acetylcholinesterase Peripheral Site That Reveals Conformational Interactions between the Peripheral and Acylation Sites

Abstract: Three-dimensional structures of acetylcholinesterase (AChE) reveal a narrow and deep active site gorge with two sites of ligand binding, an acylation site at the base of the gorge, and a peripheral site near the gorge entrance. Recent studies have shown that the peripheral site contributes to catalytic efficiency by transiently binding substrates on their way to the acylation site, but the question of whether the peripheral site makes other contributions to the catalytic process remains open. A possible role f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
177
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(189 citation statements)
references
References 27 publications
(51 reference statements)
9
177
2
1
Order By: Relevance
“…The dependence on i and i 2 was reduced when the multiple data sets were analyzed simultaneously in the SCoP program. We previously showed that the equilibrium constants corresponding to K M and i 2 for the binding of the specific Asite ligand edrophonium in its binary complex with E and its ternary complex with E and thioflavin T could be assigned unambiguously from a similar combination of fluorescence data sets (7). However, edrophonium does not show significant binding to the P-site (equivalent to eliminating ESS P in Scheme 3 and to setting iK S −1 = 0 and eliminating i as a variable in eq.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The dependence on i and i 2 was reduced when the multiple data sets were analyzed simultaneously in the SCoP program. We previously showed that the equilibrium constants corresponding to K M and i 2 for the binding of the specific Asite ligand edrophonium in its binary complex with E and its ternary complex with E and thioflavin T could be assigned unambiguously from a similar combination of fluorescence data sets (7). However, edrophonium does not show significant binding to the P-site (equivalent to eliminating ESS P in Scheme 3 and to setting iK S −1 = 0 and eliminating i as a variable in eq.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in thioflavin T fluorescence intensity between these binary and ternary complexes allows the binding of both A and P-site ligands to be quantified (7,12). To apply this approach to the reaction of carbachol with recombinant human AChE, we first compared recordings obtained with acetylthiocholine or thioflavin T. Because carbamates are poor substrates that form a slowly hydrolyzed EC intermediate (Scheme 1-Scheme 3), their reaction progress is usually monitored by changes in AChE activity with a reporter substrate like acetylthiocholine at discrete time points.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations